Diseño e implementación de un banco de pruebas de una central pico hidroeléctrica para la visualización de las variables eléctricas para la carrera de ingeniería electromecánica de la Unidad Académica CIYA período 2014 - Dávalos Constante, Andrés Alejandro (2015)
These researches is about the design and implement a test bank for a small hydroelectric generator, though the scale performing of this kind of hydroelectric central helps to understand the operating principles and the main parts, which compose it. The load test bank allows demonstrating the conversion from mechanic to electric energy; in this case the electric generation, through the leveraging of water resources, as well as visualizes, intervenes and analyzes the variables involved behavior. To observe the variables, a converter HXSP-485 RS232 a RS485, which creates a connection between the load test bank and the computer, the LabVIEW software, helped to perform a graphical interphase that improved the visualization and analysis of the load bank testing. The load test bank consists of teaching practices manual, which allows learners to analyze and take decisions related to the behavior of a hydroelectric plant. The benefit of this project is to help educators to teach in a nontraditional way, demonstrating through the load bank test located in the Electromechanical Engineering Lab, the theory learnt in classrooms, could be used into the electromechaninc engineering Lab, with the useful help of this module. Handling the elements of protection, control and warning, let learners to develop skills, this will be helpful in their professional life.